Synthesis of Activated Carbon Particles: Fabrication and Characterization of Activated carbon Particles/Urea-formaldehyde Resin - Khan, Tanveer Ahmed; Gupta, Arun; Saidatul Shima, Jamari; Yadav, Sumit Manohar (2014)
This paper addresses fabrication of activated carbon particles by pyrolysis of wood fibers and their dispersion in urea formaldehyde with an aim to optimize a stable activated carbon particles/urea formaldehyde resin. All the resin hybrids were characterized with Fourier transform infrared spectroscopy (FTIR) and power X-ray diffractometry (XRD), while the dispersion of activated carbon particles was studied with Field Emission scanning electron microscopy (FESEM). Thermo gravimetric analysis (TGA) revealed that activated carbon particles have little high effect in the thermal stability of the UF resin. From the TGA graph,it is observed that the thermal stability of the UF based activated carbon particles is higher than UF only. The scanning micrographs provided evidence of the smoother surface in the UF resin made with activated carbon particles. This was attributed to the better encapsulation of fibers by the matrix polymer.